Conformational change of syntaxin linker region induced by Munc13s initiates SNARE complex formation in synaptic exocytosis. (30th January 2017) - Wang, Shen; Choi, Ucheor B; Gong, Jihong; Yang, Xiaoyu; Li, Yun; Wang, Austin L; Yang, Xiaofei; Brunger, Axel T; Ma, Cong
Abstract: The soluble N‐ethylmaleimide‐sensitive factor attachment protein receptor (SNARE) protein syntaxin‐1 adopts a closed conformation when bound to Munc18‐1, preventing binding to synaptobrevin‐2 and SNAP‐25 to form the ternary SNARE complex. Although it is known that the MUN domain of Munc13‐1 catalyzes the transition from the Munc18‐1/syntaxin‐1 complex to the SNARE complex, the molecular mechanism is unclear. Here, we identified two conserved residues (R151, I155) in the syntaxin‐1 linker region as key sites for the MUN domain interaction. This interaction is essential for SNARE complex formation in vitro and synaptic vesicle priming in neuronal cultures. Moreover, this interaction is important for a tripartite Munc18‐1/syntaxin‐1/MUN complex, in which syntaxin‐1 still adopts a closed conformation tightly bound to Munc18‐1, whereas the syntaxin‐1 linker region changes its conformation, similar to that of the LE mutant of syntaxin‐1 when bound to Munc18‐1. We suggest that the conformational change of the syntaxin‐1 linker region induced by Munc13‐1 initiates ternary SNARE complex formation in the neuronal system. Synopsis: Munc13‐1 catalyzes the transition from the Munc18‐1/syntaxin‐1 complex to the SNARE complex critical for synaptic vesicle priming. This study shows that Munc13‐1 induces a local conformational change in the syntaxin‐1 linker region that promotes this transition. The NF residues on the MUN domain and the RI residues in the syntaxin‐1 linker region mediate a tripartite Munc18‐1/syntaxin‐1/Munc13‐1 assembly and are critical for synaptic vesicle priming. A conformational change in the syntaxin‐1 linker region induced by Munc13‐1 is sufficient for the transit of syntaxin‐1 from the closed Munc18‐1/syntaxin‐1 complex to the ternary SNARE complex. A similar conformation is present in the linker region of the syntaxin‐1 LE mutant when bound to Munc18‐1 regardless of the presence or absence of Munc13‐1. Abstract : Munc13‐1 catalyzes the transition from the Munc18‐1/syntaxin‐1 complex to the SNARE complex critical for synaptic vesicle priming. This study shows that Munc13‐1 induces a local conformational change in the syntaxin‐1 linker region that promotes this transition.